Cosplay as a form of distinction among anime and manga fans: approaches from a research executed in the Costa Rican Great Metropolitan Area - Zúñiga Valerio, Cindy (2021)
The objective of the present article is to analyze the practice of cosplay as a constitutive and distinctive practice among the existence of anime and manga fans, which are linked to this practice towards the development of an identification and a performance. The investigation was executed through ethnographical approaches between 2016 to 2019 in fans’ events. The researcher participated as an observer as well as a cosplayer and also made interviews to other cosplayers and organizational representatives. The central finding corresponds to the fact that fans generate their own parameters in regards to the practice of cosplay. They determine what a “good” or “bad” cosplay is and also determine who sustains the characteristics of a “true” fan and who does not. This is rooted from an identification and affection towards japanese animated productions, as well as the qualification of cosplay as performative due to the fact that this practice involves dressing up and acting as a certain fictional character.